Implementation of the Free Nutritional Meal Program Policy from A Good Governance Perspective in Madiun City In 2025 - Pratama, Nicko; Harianto; Agus Wiyaka; Asrifia Ridwan (Asosiasi Ahli Administrasi Indonesia, 2026)
This study aims analyze the implementation of the Free Nutritious Meal (MBG) Program in Madiun City from a good governance perspective, focusing on communication, resources, disposition, and bureaucratic structure. Although previous studies have discussed school feeding programs and policy implementation, most tend to examine them separately and rarely integrate the perspective of policy implementation theory with good governance principles at the local level. This study addresses this gap by combining George C. Edwards III’s implementation model with a good governance framework. This research uses a qualitative descriptive approach. Data were collected through interviews, observation, and documentation involving informants from the Education Office, Nutritional Fulfillment Service Unit (SPPG), and school principals, selected using purposive sampling. Data analysis follows the interactive model of Miles, Huberman, and Saldana. The results show that the implementation of the MBG Program in Madiun City has generally been effective, supported by adequate resources, clear bureaucratic structure, and positive implementer commitment. However, challenges remain in communication consistency, limited field supervision, and uneven technical understanding at the school level. From a good governance perspective, the program reflects transparency, accountability, and effectiveness, but still requires improvement in participation and coordination. This study contributes by offering an integrative analytical framework for understanding policy implementation in nutrition-based public service programs at the local level.